Non-relativistic particle higher-order harmonic radiation based short-wavelength laser and the operation stability - 罗晓华 吴木营 何为 邵明珠 罗诗裕 (Optoelectronics letters, 2011)
Under classical mechanics,the general equation of particle motion in the periodic field is derived.In the dampless case,the existence possibility of the higher-order harmonic radiation is explored by using Bessel function expansion of a generalized trigonometrical function and the multi-scale method.In the damping case,the critical properties and a chaotic behavior are discussed by the Melnikov method.The results show that the use of a higher-order harmonic radiation of non-relativistic particles as a short-wavelength laser source is perfectly possible,and the system critical condition is related to its parameters.only by adjusting parameters suitablely,the stable higher-order harmonic radiation with bigger intensity can be obtained.